Characterization of mosquito densonucleosis virus non-structural protein NS2 - Azarkh, Yevgeniy "Eugene," author; Carlson, Jonathan, advisor (Colorado State University. Libraries, 2008)
Mosquito densonucleosis viruses (or mosquito densoviruses) are insect parvoviruses that present practical interest as potential bio-insecticides and theoretical interest as a distinct parvoviral group with unique properties. Non-structural protein NS2 of the mosquito densonucleosis viruses is poorly characterized and bears no sequence similarity to NS2 proteins of other parvoviruses. It was hypothesized that mosquito densovirus NS2 is required for efficient viral propagation in cell cultures and during mosquito host infections, and that direct interactions between NS2 and other viral constituents are likely to play a role in NS2-mediated stages of viral life cycle.

Mutagenesis studies, promoter activity assays, and various imaging techniques were used to test this hypothesis and to characterize NS2 protein. Additionally, attempts were made to over-express this protein in a prokaryotic system and to characterize the recombinant NS2 protein in vitro.

It was found that NS2 mutations resulted in different phenotypes depending on the type of mutation, the route of infection initiation, and possibly on the cell type. Where abnormal phenotype was observed, decrease in efficiency of the viral DNA synthesis appeared to be a primary defect. The early stages of viral life cycle appeared to be more sensitive to NS2 mutations.

Imaging studies revealed that NS2 is targeted to the nucleus where it co-localizes and interacts with non-structural protein NS1. Nuclear localization of NS2 does not depend on other viral proteins, but requires intact carboxy-terminus of NS2.

A truncated version of NS2 protein was expressed in a prokaryotic system and tested for its ability to bind DNA. While NS2-DNA interactions have been observed, their specificity could not be determined conclusively. The assays used to study these interactions were complicated by the protein's propensity to form aggregates in vitro. It is possible that NS1-NS2 interactions documented in vivo are required for correct folding and physiological activity of NS2. This conclusion is supported by the sequence analysis of the protein's carboxy-terminus.

Further studies of mosquito densonucleosis virus non-structural protein NS2 are needed. These studies will broaden our understanding of mosquito densoviruses, which is especially important in the context of using these viruses as bio-insecticidal agents.
Keywords: FRET; IFA; mosquito densovirus; parvoviruses; viral replication; qPCR; virology